Dysregulated biosynthesis and hydrolysis of cyclic-di-adenosine monophosphate impedes sporulation and butanol and acetone production in Clostridium beijerinckii NCIMB 8052 - Awaga-Cromwell, Marian M.; Kumar, Santosh; Truong, Hieu M.; Agyeman-Duah, Eric; Okonkwo, Christopher C.; Ujor, Victor C. (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionAlthough solventogenic Clostridium species (SCS) produce butanol, achieving high enough titers to warrant commercialization of biobutanol remains elusive. Thus, deepening our understanding of the intricate cellular wiring of SCS is crucial to unearthing new targets and strategies for engineering novel strains capable of producing and tolerating greater concentrations of butanol.MethodsThis study investigated the potential role of cyclic-di-adenosine monophosphate (c-di-AMP) in regulating solvent biosynthesis in C. beijerinckii NCIMB 8052. Genes for c-di-AMP-producing and degrading enzymes [DNA integrity scanning protein A (disA) and phosphodiesterase (pde), respectively] were cloned in this organism and the recombinant strains were characterized relative to the control strain.ResultsPlasmid-borne expression of disA in C. beijerinckii led to a 1.83-fold increase in c-di-AMP levels and near complete (∼100%) inhibition of butanol and acetone biosynthesis. Conversely, c-di-AMP concentrations in the pde-expressing strain reduced 7.54-fold relative to the control with 4.20- and 2.3-fold reductions in butanol and acetone concentrations, respectively, when compared to the control strain. Relative to the control and the pde-expressing strains, the disA-expressing strain produced 1.50- and 1.90-fold more ethanol, respectively. Enzyme activity assays show that core solvent biosynthesis enzymes are mostly inhibited in vitro by exogenously supplemented c-di-AMP (50 nM). Both recombinant strains of C. beijerinckii are impaired for sporulation, particularly the disA-expressing strain.DiscussionCollectively, the results show that dysregulated production and hydrolysis of c-di-AMP severely impair butanol and acetone biosynthesis in C. beijerinckii, suggesting broader roles of this second messenger in the regulation of solventogenesis and likely, sporulation in this organism.